Inhibition of telomere recombination by inactivation of KEOPS subunit Cgi121 promotes cell longevity. - Jing Peng; Ming-Hong He; Yi-Ming Duan; Yu-Ting Liu; Jin-Qiu Zhou (PLoS Genetics, 2015)
DNA double strand break (DSB) is one of the major damages that cause genome instability and cellular aging. The homologous recombination (HR)-mediated repair of DSBs plays an essential role in assurance of genome stability and cell longevity. Telomeres resemble DSBs and are competent for HR. Here we show that in budding yeast Saccharomyces cerevisiae telomere recombination elicits genome instability and accelerates cellular aging. Inactivation of KEOPS subunit Cgi121 specifically inhibits telomere recombination, and significantly extends cell longevity in both telomerase-positive and pre-senescing telomerase-negative cells. Deletion of CGI121 in the short-lived yku80(tel) mutant restores lifespan to cgi121Δ level, supporting the function of Cgi121 in telomeric single-stranded DNA generation and thus in promotion of telomere recombination. Strikingly, inhibition of telomere recombination is able to further slow down the aging process in long-lived fob1Δ cells, in which rDNA recombination is restrained. Our study indicates that HR activity at telomeres interferes with telomerase to pose a negative impact on cellular longevity.